Government of the federal republic of Nigeria : approved budget : Vol 1 (revenue and recurrent): 1995 fiscal year - Federal republic of Nigeria; Federal republic of Nigeria (Lagos : The federal government press, 1995)
This book is the 1995 fiscal year approved revenue and current estimates of the federal government of Nigeria.
Title from cover.
osa; 02/04/19
Loans
Keywords: Revenue; Nigeria